Socio-Cultural Approach through Digital Teaching Modules: A Solution to Improve Beginning Reading Skills in Elementary Schools - Alwi, Nur Azmi; Kenedi, Ary Kiswanto; ., Arwin; Anita, Yesi; Handrianto, Ciptro; Rasool, Shahid (Journal of Ecohumanism, 2024)
The low level of early reading skills among primary school students in Indonesia is one of the significant challenges in education. International evaluations such as PISA show that Indonesian students' basic literacy skills are still below average, affecting their overall academic development. One of the contributing factors to these low results is learning that is less relevant to students' socio-cultural context. Therefore, this study aims to investigate the effect of a socio-cultural-based digital teaching module on primary school students' beginning reading skills. This study used a quasi-experimental design with a sample of 200 grade 1 students divided into experimental and control groups. The experimental group learned using socio-cultural-based digital teaching modules, while the control group applied conventional learning methods. The instrument used was a beginning reading test with 20 questions that measured the ability to recognize letter symbols, distinguish words based on the same initial letter or syllable, and compose syllables into words. Independent Sample T-Test analyzing an independent sample, ensuring that the ty and homogeneity tests were met. The results revealed significant differences between the experimental and control groups, with the experimental group showing more significant improvement in all indicators of beginning reading ability. Further discussion showed that the socio-cultural-based approach in this module made learning more relevant, exciting and interactive for students, ultimately improving their reading comprehension and motivation. In addition, integrating digital technology in this module supports flexibility and continuity of learning, allowing students to learn according to their pace and needs. This research has important implications, namely the need for broader implementation of Socio-Cultural Based Digital Teaching Modules in primary schools to improve basic literacy. However, to ensure its successful implementation, adequate technological infrastructure support and teacher training are needed to optimize this digital-based learning in the classroom.